SISTEM PENUNJANG KEPUTUSAN PENENTUAN KESESUAIAN BUDIDAYA TANAMAN PADI PULU’ MANDOTI MENGGUNAKAN METODE FORWARD CHAINING - Masnur, Masnur; Ali, Miftah (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Pulu mandoti rice plant is a rice plant that can only grow in two hamlets in Indonesia, namely Salukanan hamlet and Kandenan hamlet, Baraka sub-district, Enrekang district. There are several land data parameters that must be met so that Pulu Mandoti can grow well. Most of the farmers do not know some of these parameters. The parameters needed by the Pulu Mandoti rice plant are humidity, rainfall, altitude, soil pH, soil type, water requirements, and nutrients. So with that to be able to determine and determine the level of suitability of the Pulu Mandoti rice plant, an expert is needed. The lack of experts makes it difficult to know the level of suitability of these plants in an area. To be able to copy the ability of an expert in his field, a system is needed. The system that can be used to determine the suitability of the Pulu Mandoti rice plant is a decision support system (expert system).